A coating aluminum capable of generating far infrared and its processing technology
By using modified polyether ether ketone and modified far-infrared ceramic powder coating coating aluminum on the exterior wall coating aluminum, the problems of stain accumulation, aging, bacterial growth and ceramic powder aggregation on the surface of coated aluminum are solved, and efficient hydrophobic, antibacterial, anti-ultraviolet and infrared emission performance are achieved, significantly improving the service life of coated aluminum.
Patent Information
- Application Number
- CN202310990401.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-08-07
AI Technical Summary
The surface of the coated aluminum used in building exterior walls is prone to accumulate stains, ages under ultraviolet rays, and is prone to bacterial growth in humid environments, and far-infrared ceramic powder is prone to agglomeration in the paint and affects the infrared emission effect.
The primer is prepared by adding nano-gold, platinum, rare earth and photocatalysts to water-based paint, and the primer and far-infrared coating are coated after the aluminum surface treatment. The hydrophobic, antibacterial, anti-ultraviolet and infrared emission properties of the coating are enhanced by the preparation of modified polyether ether ketone and modified far-infrared ceramic powder.
It realizes the super-strong hydrophobic self-cleaning function of coated aluminum, broad-spectrum antibacterial properties, long-term anti-UV aging performance and excellent corrosion resistance, significantly improving the service life of coated aluminum and enhancing the infrared emission effect.
Smart Images

Figure CN117000567B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum coatings, and in particular to a coating aluminum capable of generating far infrared and a processing technology thereof. Background Art
[0002] Aluminum is widely used in various fields due to its light texture, high hardness and easy processing, among which the application in the construction field is the most extensive. The application of aluminum and aluminum alloys in construction projects can be divided into three categories: application in building structures, application in aluminum alloy doors and windows, and application in aluminum curtain walls on the exterior of buildings. The first two applications are for aluminum profiles, but the latter is for aluminum plates, and currently most of the aluminum used for building exterior walls plays a decorative role, and its functional application is temporarily rare. If you want to give aluminum functionality, the simplest way is to coat the surface of the aluminum with functional coatings. For example, the patent with publication number CN104017466B discloses a high-temperature resistant anti-corrosion coating for aluminum plates, which increases the adhesion, high-temperature resistance, and acid and alkali resistance of the anti-corrosion coating by adding modified zeolite powder to the coating formula.
[0003] For the coated aluminum used for building exterior walls, it is not only required to be resistant to corrosion and acid and alkali, but also to ensure that it will not age under ultraviolet rays and will not breed bacteria in humid environments, so as to prevent the paint on the surface of the aluminum from warping and falling off due to aging and bacterial erosion. At the same time, when used for the exterior walls of high-altitude buildings, it is also required to have the ability to be hydrophobic and self-cleaning to prevent stains from accumulating and affecting the appearance, and increase the risk of cleaning personnel working at high altitudes. Far-infrared ceramic powder is a nanomaterial that can emit infrared rays. It has the function of catalytic oxidation and can play a bactericidal role under ultraviolet rays. It also has a thermal effect different from other materials. It plays a vital role in the fields of textiles, medical care, and industry. We apply it to the preparation process of coated aluminum for building exterior walls, which can enhance the ability of coated aluminum to emit red lines, heat dissipation performance, and bactericidal performance. Conventional treatment methods for far-infrared ceramic powder include doping and coating. However, due to its moisture-absorbing properties, a large number of silanol and aluminum hydroxyl groups will be produced on the surface, which are not easy to disperse in organic solvents. Direct doping in coatings can easily cause agglomeration, affecting its own performance and easily causing the coating to fall off. Therefore, how to deal with the agglomeration of far-infrared ceramic powder in coatings and give full play to its characteristics has become an urgent problem to be solved. Summary of the invention
[0004] The purpose of the present invention is to provide a far-infrared coated aluminum and a processing technology thereof, which solves the following technical problems:
[0005] (1) The surface of coated aluminum used for building exterior walls is prone to stains, which affects the appearance of the building and causes coating aging due to long-term ultraviolet radiation; (2) The far-infrared ceramic powder in the far-infrared coating applied to the surface of aluminum is prone to agglomeration, which affects the infrared emission effect; (3) Coated aluminum used in humid environments is prone to breeding bacteria, and bacterial spores are dispersed in the air, posing a potential threat to people's health.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A processing technology for coating aluminum that can generate far infrared light comprises the following steps:
[0008] Step 1: Add nano gold, platinum, nano platinum, rare earth and photocatalyst into water-based paint, and mix well to obtain a primer;
[0009] Step 2: Surface-treat the aluminum material, apply primer after drying, apply far-infrared paint after drying, let stand for 10-15 minutes after drying again, and roll it up to obtain coated aluminum that generates far-infrared.
[0010] Furthermore, in step one, the water-based paint is any one of epoxy resin water-based paint and polyurethane water-based paint.
[0011] Furthermore, the preparation method of the far-infrared coating is:
[0012] Mix modified polyetheretherketone and isophorone diisocyanate, introduce nitrogen, add dibutyltin dilaurate, stir and mix evenly at room temperature, heat to 50-60°C and react for 1-2h, add 1,4-butanediol, continue to heat to 70-80°C and react for 0.5-1h, add modified far-infrared ceramic powder, cool to 40-45°C, add triethylamine, react for 1-2h, add water, stir at a rate of 300-500r / min for 3-5h, and obtain far-infrared coating after natural defoaming.
[0013] Furthermore, the preparation method of the modified polyetheretherketone is:
[0014] S1: placing polyetheretherketone in chloroform, stirring to fully dissolve it, passing nitrogen protection, adding epichlorohydrin and anhydrous tin tetrachloride, heating to 60-70°C for reaction for 24-48h, cooling to room temperature, pouring the product into ice water, filtering the precipitate, washing and drying to obtain epoxidized polyetheretherketone;
[0015] S2: Add epoxidized polyetheretherketone to N,N-dimethylformamide, stir for 1-2h, add perfluorobutylethanol and catalyst①, heat to 55-65℃, react for 3h, filter, wash and vacuum dry to obtain modified polyetheretherketone.
[0016] Through the above technical scheme, under the action of anhydrous tin tetrachloride, polyetheretherketone and epichlorohydrin undergo Friedel-Crafts alkylation reaction, and the hydrogen atoms on the benzene ring are replaced by alkyl groups to obtain epoxidized polyetheretherketone. Under the action of tetrabutylammonium bromide, the epoxy groups in its structure undergo ring-opening reaction with the hydroxyl groups in the perfluorobutylethanol structure to obtain modified polyetheretherketone. The polyetheretherketone has excellent corrosion resistance. After modification, a large number of fluorine atoms are introduced into its structure to increase its hydrophobicity. The introduced hydroxyl groups can participate in the preparation process of far-infrared coating, making it more compatible with the far-infrared coating. Even if it is used for a long time, phase separation will not occur, so that the prepared far-infrared coating can have both anti-fouling, self-cleaning and corrosion resistance properties, and significantly improve the service life of the far-infrared coating.
[0017] Furthermore, it is characterized in that, in step S2, the catalyst ① is tetrabutylammonium bromide.
[0018] Furthermore, the preparation method of the modified far-infrared ceramic powder comprises the following steps:
[0019] SS1: Place the far-infrared ceramic powder in anhydrous ethanol, add KH792, ultrasonically disperse for 30-50 minutes, add oxalic acid to adjust the pH to 4-5, ultrasonically disperse for 10-20 minutes, heat in a water bath at 70-80°C for 2-5 hours, cool to room temperature, and vacuum dry to obtain the amino far-infrared ceramic powder;
[0020] SS2: Place the amino far-infrared ceramic powder in anhydrous ethanol, ultrasonically disperse for 10-20 minutes, add 3,3',4,4'-benzophenonetetracarboxylic dianhydride and catalyst ②, heat to 70-80°C, stir for 5-8 hours, and vacuum dry to obtain the modified far-infrared ceramic powder.
[0021] Through the above technical scheme, under the action of aminosilane coupling agent, amino groups are grafted on the surface of far-infrared ceramic powder, and under the action of triethylamine, the amino groups on its surface react with the anhydride groups in 3,3',4,4'-benzophenonetetracarboxylic dianhydride to obtain modified far-infrared ceramic powder. The surface of the modified far-infrared ceramic powder has carboxyl groups, which can participate in the preparation process of far-infrared coating in a chemical bonding manner, so that it can be evenly dispersed in the matrix and is not prone to agglomeration, thereby improving the infrared emitting ability of the far-infrared coating and enhancing the antibacterial and heat dissipation properties of the far-infrared coating. At the same time, the benzophenone group introduced on the surface of the modified far-infrared ceramic powder has excellent UV resistance, which can enhance the UV aging resistance of the far-infrared coating and further increase its service life.
[0022] Furthermore, in step SS1, the concentration of the added oxalic acid is 1-2 mol / L.
[0023] Furthermore, in step S2, the catalyst ② is triethylamine.
[0024] A coated aluminum that generates far infrared radiation, made from any of the above.
[0025] Beneficial effects of the present invention:
[0026] The present invention prepares coated aluminum by coating far-infrared paint on the surface of aluminum material, so that the coated aluminum has super hydrophobic self-cleaning function, broad-spectrum antibacterial property, long-term anti-ultraviolet aging property, and excellent corrosion resistance. When used for building exterior walls, the problem of coating warping and falling off caused by ultraviolet aging, rainwater and acid rain scouring and corrosion in extreme weather can be avoided. In addition, due to the super hydrophobic self-cleaning function of the coated aluminum surface, the attachment sites of dust and bacteria can be reduced, and the damage caused by the erosion of the coating by bacterial reproduction and growth can be effectively avoided. The internal aluminum material can be protected for a longer period of time, and the service life of the coated aluminum is greatly improved. At the same time, since the far-infrared ceramic powder that can emit infrared rays has almost no agglomeration phenomenon and is evenly dispersed on the surface of the coated aluminum, the normal total radiation emissivity of the far-infrared ceramic powder is improved, so that the coated aluminum has excellent infrared emission effect, and can further improve the antibacterial and heat dissipation performance of the coated aluminum, so that the temperature inside the building is reduced, and a comfortable living environment is provided for people in the hot summer.
[0027] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0029] Figure 1 IR spectra of epoxidized polyetheretherketone and modified polyetheretherketone in Example 1 of the present invention;
[0030] Figure 2 This is a thermal gravimetric curve of the far-infrared ceramic powder, the amino far-infrared ceramic powder, and the modified far-infrared ceramic powder in Example 1 of the present invention. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Example 1
[0033] 1. Preparation of modified polyetheretherketone
[0034] S1: 2 g of polyetheretherketone was placed in 80 ml of chloroform, stirred to fully dissolve, nitrogen was introduced for protection, 2.5 ml of epichlorohydrin and 1.5 ml of anhydrous tin tetrachloride were added, the temperature was raised to 60 ° C for reaction for 24 h, cooled to room temperature, the product was poured into ice water, the precipitate was filtered, washed and dried to obtain epoxidized polyetheretherketone;
[0035] S2: Add 2.5 g of epoxidized polyetheretherketone to 100 ml of N,N-dimethylformamide, stir for 1 hour, add 2 ml of perfluorobutylethanol and 0.5 g of tetrabutylammonium bromide, heat to 55°C, react for 3 hours, filter, wash, and vacuum dry to obtain modified polyetheretherketone.
[0036] Epoxidized polyetheretherketone and modified polyetheretherketone were characterized by infrared spectroscopy. Figure 1 It can be seen that in the infrared spectrum of epoxidized polyetheretherketone, 3037cm -1 The absorption peak of the carbon-hydrogen bond in the benzene ring is at 913 cm -1 The characteristic absorption peak of epoxy group appeared at 1244cm -1 The absorption peak of the carbon-oxygen bond in the epoxy group appeared at 913 cm -1 The characteristic absorption peak of epoxy group is at 1244 cm -1 The carbon-oxygen bond absorption peak in the epoxy group disappears, 3221cm -1 The absorption peak of hydroxyl group appeared at the position, indicating that the epoxy group in the epoxidized polyetheretherketone structure and the hydroxyl group in the perfluorobutylethyl alcohol structure underwent a ring-opening reaction.
[0037] 2. Preparation of modified far-infrared ceramic powder
[0038] SS1: 3 g of far-infrared ceramic powder was placed in 50 ml of anhydrous ethanol, 3.5 ml of KH792 was added, and ultrasonic dispersion was performed for 30 min. 1 mol / L oxalic acid was added to adjust the pH to 4, and ultrasonic dispersion was performed for 10 min. The mixture was heated in a water bath at 70°C for 2 h, cooled to room temperature, and vacuum dried to obtain amino far-infrared ceramic powder.
[0039] SS2: Place 3 g of amino-modified far-infrared ceramic powder in 50 ml of anhydrous ethanol, ultrasonically disperse for 10 min, add 2 g of 3,3',4,4'-benzophenonetetracarboxylic dianhydride and 0.5 ml of triethylamine, heat to 70 °C, stir for 5 h, and vacuum dry to obtain modified far-infrared ceramic powder.
[0040] Thermogravimetric analysis was performed on far-infrared ceramic powder, amino far-infrared ceramic powder and modified far-infrared ceramic powder. Figure 2 It can be seen that at a high temperature of 800°C, the final mass retention rate of the far-infrared ceramic powder is 98.3%, and the lost part is caused by the decomposition of the crystalline water in the structure; the final mass retention rate of the amination far-infrared ceramic powder is 46.15%, and the lost part is caused by the thermal decomposition of the silane coupling agent grafted on its surface; the final mass retention rate of the modified far-infrared ceramic powder is 27.6%, and the lost part is caused by the thermal decomposition of the organic matter grafted on its surface.
[0041] 3. Preparation of far-infrared coating
[0042] Mix 5 ml of modified polyetheretherketone and 6 ml of isophorone diisocyanate, introduce nitrogen, add 0.2 g of dibutyltin dilaurate, stir and mix evenly at room temperature, heat to 50 ° C to react for 1 hour, add 1 ml of 1,4-butanediol, continue to heat to 70 ° C to react for 0.5 hour, add 3 g of modified far-infrared ceramic powder, cool to 40 ° C, add 0.15 ml of triethylamine, react for 1 hour, add 50 ml of water, stir at a rate of 300 r / min for 3 hours, and obtain a far-infrared coating after natural defoaming.
[0043] Example 2
[0044] Preparation of far-infrared coating
[0045] Mix 8 ml of modified polyetheretherketone and 8.5 ml of isophorone diisocyanate, introduce nitrogen, add 0.25 g of dibutyltin dilaurate, stir and mix evenly at room temperature, heat to 55 ° C and react for 1.5 hours, add 1.5 ml of 1,4-butanediol, continue to heat to 75 ° C and react for 0.8 hours, add 3.5 g of modified far-infrared ceramic powder, cool to 43 ° C, add 0.2 ml of triethylamine, react for 1.5 hours, add 60 ml of water, stir at a rate of 400 r / min for 4 hours, and obtain a far-infrared coating after natural defoaming.
[0046] Wherein, the preparation method of the modified polyetheretherketone and the modified far-infrared ceramic powder is the same as that in Example 1.
[0047] Example 3
[0048] Preparation of far-infrared coating
[0049] Mix 10 ml of modified polyetheretherketone and 9.5 ml of isophorone diisocyanate, introduce nitrogen, add 0.3 g of dibutyltin dilaurate, stir and mix evenly at room temperature, heat to 60 ° C and react for 2 h, add 2 ml of 1,4-butanediol, continue to heat to 80 ° C and react for 1 h, add 4 g of modified far-infrared ceramic powder, cool to 45 ° C, add 0.3 ml of triethylamine, react for 2 h, add 65 ml of water, stir at a rate of 500 r / min for 5 h, and obtain a far-infrared coating after natural defoaming.
[0050] Wherein, the preparation method of the modified polyetheretherketone and the modified far-infrared ceramic powder is the same as that in Example 1.
[0051] Comparative Example 1
[0052] Preparation of far-infrared coating
[0053] Mix 8 ml of polytetramethylene glycol and 8.5 ml of isophorone diisocyanate, introduce nitrogen, add 0.25 g of dibutyltin dilaurate, stir and mix evenly at room temperature, heat to 55 ° C and react for 1.5 hours, add 1.5 ml of 1,4-butanediol, continue to heat to 75 ° C and react for 0.8 hours, add 3.5 g of modified far-infrared ceramic powder, cool to 43 ° C, add 0.2 ml of triethylamine, react for 1.5 hours, add 60 ml of water, stir at a rate of 400 r / min for 4 hours, and obtain a far-infrared coating after natural defoaming.
[0054] Wherein, the preparation method of the modified far-infrared ceramic powder is the same as that in Example 1.
[0055] Comparative Example 2
[0056] Preparation of far-infrared coating
[0057] Mix 8 ml of modified polyetheretherketone and 8.5 ml of isophorone diisocyanate, pass nitrogen, add 0.25 g of dibutyltin dilaurate, stir and mix evenly at room temperature, heat to 55 ° C and react for 1.5 hours, add 1.5 ml of 1,4-butanediol, continue to heat to 75 ° C and react for 0.8 hours, add 3.5 g of pentaerythritol, cool to 43 ° C, add 0.2 ml of triethylamine, react for 1.5 hours, add 60 ml of water, stir at a rate of 400 r / min for 4 hours, and obtain a far-infrared coating after natural defoaming.
[0058] The preparation method of the modified polyetheretherketone is the same as that in Example 1.
[0059] Comparative Example 3
[0060] Preparation of far-infrared coating
[0061] Mix 8 ml of polytetramethylene glycol and 8.5 ml of isophorone diisocyanate, introduce nitrogen, add 0.25 g of dibutyltin dilaurate, stir and mix evenly at room temperature, heat to 55 ° C and react for 1.5 hours, add 1.5 ml of 1,4-butanediol, continue to heat to 75 ° C and react for 0.8 hours, add 3.5 g of pentaerythritol, cool to 43 ° C, add 0.2 ml of triethylamine, react for 1.5 hours, add 60 ml of water, stir at a rate of 400 r / min for 4 hours, and obtain a far-infrared coating after natural defoaming.
[0062] Comparative Example 4
[0063] Preparation of far-infrared coating
[0064] Mix 8 ml of modified polyetheretherketone and 8.5 ml of isophorone diisocyanate, pass nitrogen, add 0.25 g of dibutyltin dilaurate, stir and mix evenly at room temperature, heat to 55 ° C and react for 1.5 hours, add 1.5 ml of 1,4-butanediol, continue to heat to 75 ° C and react for 0.8 hours, add 3.5 g of far-infrared ceramic powder, cool to 43 ° C, add 0.2 ml of triethylamine, react for 1.5 hours, add 60 ml of water, stir at a rate of 400 r / min for 4 hours, and obtain a far-infrared coating after natural defoaming.
[0065] The preparation method of the modified polyetheretherketone is the same as that in Example 1.
[0066] Performance testing:
[0067] The far-infrared coatings prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were cured at 80° C. for 2 h to prepare samples that met the specifications. The samples were tested for normal radiance using a TSS-5X far-infrared emissivity tester. The samples were tested for thermal conductivity using reference standard GB / T10297-2015. The samples were tested for salt spray resistance using reference standard GB / T1771-2007. The samples were placed in an ultraviolet light environment with a wavelength of 313 nm and an irradiance of 0.72 / m 2 After 120 hours in the UV aging box, the aging grade of the samples after UV aging treatment was evaluated according to the reference standard GB / T1766-2008; the antibacterial performance of the samples was tested according to the reference standard GB / T31402-2015; the water contact angle of the samples was tested using the JC2000D2G contact angle tester; the specific test results are shown in the table below:
[0068]
[0069] As can be seen from the above table, the samples prepared in Examples 1 to 3 have excellent effects in infrared emission, lowering indoor temperature, corrosion resistance, anti-ultraviolet aging, antibacterial and self-cleaning. The samples prepared in Comparative Examples 1 and 3 do not add modified polyetheretherketone, so they are at a relatively poor level in corrosion resistance and hydrophobic self-cleaning. The samples prepared in Comparative Example 1 are stronger in various properties than those prepared in Comparative Example 3, especially in infrared emission, anti-ultraviolet aging and antibacterial capabilities. This is because the samples prepared in Comparative Example 1 also add modified far-infrared ceramic powder, and the samples prepared in Comparative Examples 2 and 3 have better infrared emission, cooling in buildings, anti-ultraviolet aging and antibacterial properties. Both are at a poor level, because neither of them adds modified far-infrared ceramic powder. The difference from the sample prepared in Comparative Example 3 is that the sample prepared in Comparative Example 2 adds modified polyetheretherketone, so its corrosion resistance and hydrophobic self-cleaning performance are better than those in Comparative Example 3. Compared with the sample prepared in Example 2, the sample prepared in Comparative Example 4 has much lower infrared emitting ability and antibacterial and anti-ultraviolet ability than the sample prepared in Example 2, because in the sample prepared in Comparative Example 4, far-infrared ceramic powder with infrared emitting function is directly added without modification, so agglomeration occurs in the matrix, resulting in its infrared emitting ability, antibacterial property and anti-ultraviolet aging ability being at a poor level.
[0070] The far-infrared coating prepared in Examples 1 to 3 is used to prepare coated aluminum that generates far-infrared, which specifically includes the following steps:
[0071] Step 1: Add 0.01g of nano-gold, 0.2g of platinum, 0.03g of nano-platinum, 0.01g of rare earth and 0.03g of photocatalyst into 50ml of water-based paint and mix well to obtain a primer;
[0072] Step 2: Surface treatment of aluminum, coating with primer after drying, coating with far-infrared coating after drying, drying again, standing for 10 minutes, and rolling up to obtain far-infrared coated aluminum
[0073] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0074] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A processing technology for coating aluminum that can generate far infrared, characterized in that: The following steps are involved: Step 1: Add nano gold, platinum, nano platinum, rare earth and photocatalyst into water-based paint, and mix well to obtain a primer; Step 2: Surface treatment of the aluminum material, coating with primer after drying, coating with far-infrared paint after drying, drying again, standing for 10-15 minutes, and rolling up to obtain coated aluminum that generates far-infrared; The preparation method of the far-infrared coating is: Modified polyetheretherketone and isophorone diisocyanate are mixed, nitrogen is introduced, dibutyltin dilaurate is added, the mixture is stirred and mixed evenly at room temperature, the temperature is raised to 50-60°C for reaction for 1-2h, 1,4-butanediol is added, the temperature is further raised to 70-80°C for reaction for 0.5-1h, modified far-infrared ceramic powder is added, the temperature is lowered to 40-45°C, triethylamine is added, the mixture is reacted for 1-2h, water is added, the mixture is stirred at a rate of 300-500r / min for 3-5h, and the far-infrared coating is obtained after natural defoaming; The preparation method of the modified polyetheretherketone is: S1: placing polyetheretherketone in chloroform, stirring to fully dissolve it, passing nitrogen protection, adding epichlorohydrin and anhydrous tin tetrachloride, heating to 60-70°C for reaction for 24-48h, cooling to room temperature, pouring the product into ice water, filtering the precipitate, washing and drying to obtain epoxidized polyetheretherketone; S2: Add epoxidized polyetheretherketone to N,N-dimethylformamide, stir for 1-2h, add perfluorobutylethanol and catalyst ①, heat to 55-65°C, react for 3h, filter, wash, and vacuum dry to obtain modified polyetheretherketone; The preparation method of the modified far-infrared ceramic powder comprises the following steps: SS1: Place the far-infrared ceramic powder in anhydrous ethanol, add KH792, ultrasonically disperse for 30-50 minutes, add oxalic acid to adjust the pH to 4-5, ultrasonically disperse for 10-20 minutes, heat in a water bath at 70-80°C for 2-5 hours, cool to room temperature, and vacuum dry to obtain the amino far-infrared ceramic powder; SS2: Place the amino far-infrared ceramic powder in anhydrous ethanol, ultrasonically disperse for 10-20 minutes, add 3,3',4,4'-benzophenonetetracarboxylic dianhydride and catalyst ②, heat to 70-80°C, stir for 5-8 hours, and vacuum dry to obtain the modified far-infrared ceramic powder.
2. The processing technology of coating aluminum that can generate far infrared according to claim 1 is characterized in that: In step 1, the water-based paint is any one of epoxy resin water-based paint and polyurethane water-based paint.
3. The processing technology of coating aluminum that can generate far infrared according to claim 1 is characterized in that: In step S2, the catalyst ① is tetrabutylammonium bromide.
4. The processing technology of coating aluminum that can generate far infrared according to claim 1 is characterized in that: In step SS1, the concentration of the added oxalic acid is 1-2 mol / L.
5. The processing technology of coating aluminum that can generate far infrared according to claim 1 is characterized in that: In step S2, the catalyst ② is triethylamine.
6. A coated aluminum that generates far infrared, characterized in that: The invention is prepared by the processing technology described in any one of claims 1 to 5.
Citation Information
Patent Citations
A high temperature resistant anticorrosion coating for aluminum plate
CN104017466B
Nano far-infrared ceramic powder loading super thermal insulation coating and preparation method therefor
CN105001754A
Environment-friendly coating with heat insulation and corrosion prevention functions
CN112852240A